Mastering Red Hat Linux 7.1 - Danesh, Arman (Sybex, 2001)
This book is designed as an introduction to the installation and use of Linux based on Red Hat Linux 7.1 is a widely used version of Linux that is well suited to use on server systems, as well as Linux workstations and desktop computer.